PP.27.24: FAMILIAL TAKAYASU ARTERITIS IN TWIN SISTERS. (June 2015) - Kefi, A.; Daoud, F.; Aydi, Z.; Dhaou, B. Ben; Baili, L.; Boussema, E.; Boussema, F.
Abstract : Objective: Takayasu arteritis (TA) is a rare chronic vasculitis of the aorta and its branches. Infections, autoimmunity and genetic factors, as suggested by family clustering, may play a role in its pathogenesis. In this report, we describe familial TA in twin Tunisian sisters. Design and method: TA was diagnosed according the classification of the criteria of the American College of Rheumatology 1990. Results: Case1: A female patient (twin A) born to non-consanguineous parents, with no remarkable family history, had been diagnosed in our department with TA at the age of 16, after presenting with syncopal attacks, absent radial pulse, 4-limb blood pressure inequality and persistently raised inflammatory markers. Catheter and computed tomography (CT) angiography revealed stenotic abnormalities of both subclavian arteries. She was started on corticosteroids and had a carotid-humeral bypass. Over the next several months, she developed more stenosis of the central retinal, the left subclavian, the right humeral arteries, the aortic arch, and the carotid-humeral bypass. The management included corticosteroids, cyclophosphamide and surgical treatment. In 2001, she was readmitted with a setting of sudden right hemiplegia and aphasia. On investigation, she had an ischemic stroke by occlusion of the left middle cerebral artery. She received aspirin and corticosteroids. Until now, lesions remain stable. Case 2: A 32-year-old female patient (twin B), previously asymptomatic, presented to our department on November 2014 with complaints of claudication of the upper extremities, pulselessness in both brachial arteries, recurrent gastrointestinal complaints of abdominal pain, diarrhea and weight loss. She was found to have elevated blood inflammatory markers. Funduscopie examination showed pale optic disks and narrowing of retinal arteries. CT angiography exhibited stenosis of both common carotid arteries, and a superior mesenteric artery occlusion with recovery by the collateral arteries. There were no others specific manifestations of the TA. The patient received corticosteroids with a favorable evolution. Conclusions: Although rare, familial TA is an important clinical entity. To prevent delayed diagnosis and serious sequelae, a screening using pulse check and non-invasive imaging should be considered in family members of the affected patients.